2019
DOI: 10.1002/joom.1052
|View full text |Cite
|
Sign up to set email alerts
|

Work after work: The impact of new service delivery models on work hours

Abstract: In many professional service organizations (PSOs), a single server such as a physician or lawyer delivers services to customers across multiple channels. In these settings, there exists a risk that work obligations encroach on the personal lives of the servers. We empirically examine this concern in the primary care setting of physicians providing care to patients following the introduction of a new service delivery channel, e‐visits. Our data cover an 8.5‐year timespan and include 3.3 million patient encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 91 publications
(102 reference statements)
1
21
0
Order By: Relevance
“…Such instances reveal potentially missed opportunities by otherwise excellent OM contributions to add to our understanding of public policy. For instance, Bavafa and Terwiesch (2019) showed that the introduction of an additional service‐delivery channel (e‐visits) for physicians nearly doubles their number of work hours, consequently encroaching on their personal lives. The authors acknowledged the immense potential implications of their work for public policy.…”
Section: Current State Of Relationship Between Om Research and Public Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Such instances reveal potentially missed opportunities by otherwise excellent OM contributions to add to our understanding of public policy. For instance, Bavafa and Terwiesch (2019) showed that the introduction of an additional service‐delivery channel (e‐visits) for physicians nearly doubles their number of work hours, consequently encroaching on their personal lives. The authors acknowledged the immense potential implications of their work for public policy.…”
Section: Current State Of Relationship Between Om Research and Public Policymentioning
confidence: 99%
“…Our hope is that editors will yet encourage public‐policy ideas with the necessary caveats, even if somewhat speculative, on research with public‐policy implications. For example, in Bavafa and Terwiesch (2019), a relatively simple approach the authors have since observed in practice is to limit e‐visit hours, and all electronic communication with a doctor, explicitly to a specific time frame (e.g., 4–5 p.m. every day). Whether such a requirement would be appropriate as public policy is not clear but may generate work‐life balance benefits to burdened providers.…”
Section: Current State Of Relationship Between Om Research and Public Policymentioning
confidence: 99%
“…For the RQ3:"During which periods do employees work during non-work times? ", we found in existing literature (Mar & Buzeti, 2021;CIPD, 2020;Bavafa & Terwiesch, 2019;ILO & Eurofound, 2017) that employees work at different times during non-work times.…”
Section: Resultsmentioning
confidence: 77%
“…As we know from practice the performance of work during non-work has expanded with the mass use of ICT at work and the problem started to be more visible because of mass spread of remote work during COVID-19 pandemic. We found and identified 18 scientific literature on the selected topic of work during non-work time (Andrade and Matias, 2021;Lee et al, 2021;Mar and Buzeti, 2021;Wendsche, de Bloom, Syrek and Vahle--Hinz, 2021;CIPD, 2020;Lutz et al, 2020;Mohd Fauzi et al, 2020;Bavafa and Terwiesch, 2019;Eurofound and ILO, 2019;Schmoll, 2019;Thulin, Vilhelmson and Johansson, 2019;Gadeyne et al 2018;Houdmont et al, 2018;ILO and Eurofound, 2017;Ďuranová and Ohly, 2016;Eurofound, 2016;Kreiner, 2006). Based on the research questions (RQ), we have analysed the following literature: RQ1: How is work during non-work times becoming more widespread among employees?…”
Section: Methodological Approach and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation